Asymmetric Information in Public Provision Mechanisms - Gianluca Fiorentini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
An optimal mechanism fot the provision of impure public inputs to oligopolistic firms is investigated using a three stage game where in the first stage the public agency which provides the public input fixes a non-linear price schedule.
Keywords: 330